2023
DOI: 10.3122/jabfm.2022.220416r1
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Non-Prescription Antibiotic Use among Hispanic Patients in the Houston Metroplex

Abstract: Background: Non-prescription antibiotic use includes taking an antibiotic without medical guidance (e.g., leftovers, from friends/relatives, or purchased without a prescription). Non-prescription use contributes to antimicrobial resistance, adverse drug reactions, interactions, superinfection, and microbiome imbalance. Qualitative studies exploring perspectives regarding non-prescription use among Hispanic patients are lacking. We used the Kilbourne Framework for Advancing Health Disparities Research to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Our findings also highlight some specific healthcare barriers, including the high costs of doctor visits, long clinic waits (e.g., to schedule appointments or during doctor visits), and a lack of health insurance or health coverage, which impact Hispanic patients’ decisions to use non-prescription antibiotics [ 3 , 12 ]. Patients who experience the burden of high costs during a doctor’s visit also had three times higher intended non-prescription antibiotic use from the US and friends and relatives in comparison to patients that did not report high costs during a doctor’s visit as a problem.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings also highlight some specific healthcare barriers, including the high costs of doctor visits, long clinic waits (e.g., to schedule appointments or during doctor visits), and a lack of health insurance or health coverage, which impact Hispanic patients’ decisions to use non-prescription antibiotics [ 3 , 12 ]. Patients who experience the burden of high costs during a doctor’s visit also had three times higher intended non-prescription antibiotic use from the US and friends and relatives in comparison to patients that did not report high costs during a doctor’s visit as a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also found that individuals without health insurance were over three times more likely to purchase antibiotics outside the US, presumably without a prescription [ 11 ]. In our previous qualitative study, high copayments (for a doctor’s visit and subsequent prescription medications), regardless of patients having healthcare coverage, drove some patients to seek informal medical advice and source non-prescription medications using their social networks [ 12 ]. Future research should leverage and promote appropriate antibiotic use as a social norm for Hispanic patients with and without healthcare coverage [ 13 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations